New Technologies and Edible Coatings for Minimally Processed and Refrigerated (MPR) Fruits and Vegetables (Fresh Cuts and Freshly Squeezed Juices) - Güneş, Gürbüz; Turan, Deniz (Springer US, 2017)
The demand for minimally processed fresh fruits and vegetable products by consumers has been increasing around the world. Minimally processed fruits and vegetables are convenient fresh products with high nutritional quality. They are prone to microbiological and biochemical degradations, and thus, technologies to prevent these degradations without adversely affecting the fresh quality are desired. Conventional thermal preservation treatments are not suitable for these products. Several emerging nonthermal technologies have great potential alone or in combination for preserving minimally processed fresh produce products. This chapter provides a brief overview of the nonthermal technologies such as ozone, electrolyzed water, gamma irradiation, ultraviolet light (UVC), pulsed light, ultrasound, cold plasma, dense-phase CO2 processing, high-pressure processing, pulsed electric field, and edible coatings. Their applications alone or in combination on minimally processed fresh produce products including fresh cuts and freshly squeezed juices are discussed.